A Monetary Reward Alters Pacing but Not Performance in Competitive Cyclists - Skorski, Sabrina; Thompson, Kevin G.; Keegan, Richard J.; Meyer, Tim; Abbiss, Chris R. (Frontiers in Physiology, 2017)
Money has frequently been used as an extrinsic motivator since it is assumed that humans are willing to invest more effort for financial reward. However, the influence of a monetary reward on pacing and performance in trained athletes is not well understood. Therefore, the aim of this study was to analyse the influence of a monetary reward in well-trained cyclists on their pacing and performance during short and long cycling time trials (TT). Twentythree cyclists (6 F, 17 M) completed 4 self-paced time trials (TTs, 2 short: 4 km & 6 min; 2 long: 20 km and 30 min); in a randomised order. Participants were separated into parallel, non-randomised “rewarded” and “non-rewarded” groups. Cyclists in the rewarded group received a monetary reward based on highest mean power output across all TTs. Cyclists in the non-rewarded group did not receive a monetary reward. Overall performance was not significantly different between groups in short or long TTs (p>0.48). Power output showed moderatly lower effect sizes at comencement of the short TTs (Pmeandiff = 36.6 W; d>0.44) and the 20km TT (Pmeandiff = 22.6 W; d = 0.44) in the rewarded group. No difference was observed in pacing during the 30min TT (p = 0.95). An external reward seems to have influenced pacing at the commencement of time trials. Participants in the non-rewarded group adopted a typical parabolic shaped pattern, whereas participants in the rewarded group started trials more conservatively. Results raise the possibility that using money as an extrinsic reward may interfere with regulatory processes required for effective pacing.